Synthesis of Rofecoxib and Study of Lactone Ring Stability - R. Sharma, Niraj; Rawat, G.S. (Asian Journal of Chemistry, 2016)
The synthesis of Rofecoxib [4-(4'-Methyl Sulfonyl Phenyl)-3-Phenyl-2-(5H) Furanone] was carried out and various combination of solvents were tried to study the stability of the lactone ring during one pot cyclization of the lactone ring. It was found that removal of water from the reaction mixture during the reaction prevents the lactone ring from decomposing and thereby avoiding any byproducts formation. Also the product was isolated from the reaction mixture by an improved method thereby facilitating the recovery of the organic base salt and hence providing a good commercial manufacturing process for Rofecoxib.